This motherless land [large type] - May, Nikki (Read with Jenna., 2024)
When Funke's mother dies in a tragic accident in Lagos, she's sent to live with her maternal family in England. Traumatised by grief and against a backdrop of condescension and mild neglect, conformist Funke strives to fit in, determined to become one of them. Free-spirited Liv has always wanted to break free of her joyless family, resolved to be nothing like them. Fiercely protective of Funke, she at last has a purpose, and an ally. The two cousins give each other what they need most: love. But the past casts long shadows and the choices made by their mothers haunt Funke and Liv, shaping the trajectory of their adult lives. Can they escape their legacy?